Męczennik jako świadek na podstawie akt męczenników - Wysocki, Marcin (Verbum Vitae, 2015)
The article explores the phenomenon of Christian testimony present in experiences of persecution and in the death of martyrs, those who have given their lives for Christ. The primary sources for our reflection are the preserved descriptions of martyrdom (passio, acta martyrum). Martyrdom is commonly considered as the highest form of Christian testimony, thus it is useful to examine how it is present in the direct testimonies of the passion and death of the Christians of the first centuries, in that period of persecutions when indeed the theology of martyrdom first awakened and the witness of a Christian’s life and death took on particular importance. The article discusses the issue of testimony from different points of view: the witness of written testimonies, the testimony of the earthly lives of the martyrs, the testimony of their faith, and testimony of the act of martyrdom itself.